The complete genome sequence of unculturable Mycoplasma faucium obtained through clinical metagenomic next-generation sequencing - Sabat, Artur J.; Durfee, Tim; Baldwin, Schuyler; Akkerboom, Viktoria; Voss, Andreas; Friedrich, Alexander W.; Bathoorn, Erik (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Diagnosing Mycoplasma faucium poses challenges, and it's unclear if its rare isolation is due to infrequent occurrence or its fastidious nutritional requirements. Methods This study analyzes the complete genome sequence of M. faucium, obtained directly from the pus of a sternum infection in a lung transplant patient using metagenomic sequencing. Results Genome analysis revealed limited therapeutic options for the M. faucium infection, primarily susceptibility to tetracyclines. Three classes of mobile genetic elements were identified: two new insertion sequences, a new prophage (phiUMCG-1), and a species-specific variant of a mycoplasma integrative and conjugative element (MICE). Additionally, a Type I Restriction-Modification system was identified, featuring 5’-terminally truncated hsdS pseudogenes with overlapping repeats, indicating the potential for forming alternative hsdS variants through recombination. Conclusion This study represents the first-ever acquisition of a complete circularized bacterial genome directly from a patient sample obtained from invasive infection of a primary sterile site using culture-independent, PCR-free clinical metagenomics.